PENGGUNAAN TEKNOLOGI INFORMASI DALAM PELAYANAN SIRKULASI DI PERPUSTAKAAN - Eviendrita Eviendrita (Maktabatuna, 2019)
Libraries are services, so there is no library without services.The service here means the user of library services. This kind of work activity is often referred to as "circulation",which implies circulating library collections to users. In library science, circulation is often known as borrowing. However, the notion of circulation services actually includes all forms of recording activities related to utilization, the use of library collections quickly and timely for the benefit of users of library services. The purpose of the library to provide services to the readers is so that library materials that have been collected and processed as well as possible can reach the readers.The existence of information technology is clearly that there is a part of work that can be facilitated with help or technology. This activity is called library automation. The use of information technology can provide easy access for users and improve library services. One of them is circulation service that uses the OPAC system. OPAC is an acronym for online catalog access for the public. Users can access remotely via the web or LAN or directly through a computer that is provided specifically for online catalogs in a library.